Relationship of Nutrition Knowledge and Chronic Energy Loss With Anemia in Pregnant Women in Alalak Selatan Health Center - Utami, Syahrida Wahyu; Nadiantari, Wahyu; Ari Lestari, Nur Cahyani (JOURNAL EDUCATIONAL OF NURSING(JEN), 2021)
Anemia is an indicator of poor nutrition and health. The most common cause of anemia worldwide is iron deficiency, due to a prolonged iron imbalance caused by iron intake or food intake that is not strong. Iron deficiency anemia in pregnant women can affect the growth and development of the fetus or baby during pregnancy and afterwards. Factors that influence anemia in pregnant women include knowledge and direct factors that influence the incidence of anemia in pregnant women, namely the risk of chronic energy shortage (CES). The research objective to be achieved based on the above problem formulation is to know the relationship between nutritional knowledge and chronic energy shortages with anemia in pregnant women at Alalak Selatan Health Center. The study uses a quantitative descriptive design using accidental sampling technique approach by taking respondents who come to Alalak Selatan Health Center 2. Samples used in this study as many as 57 respondents, with data analysis using the Chi Square test. The results showed a significance of 0,000